Health facility assessments of cervical cancer prevention, early diagnosis, and treatment services in Gulu, Uganda - Tana Chongsuwat; Aaliyah O. Ibrahim; Ann E. Evensen; James H. Conway; Margaret Zwick; William Oloya (Public Library of Science (PLoS), 2023)
Background Cervical cancer is ranked globally in the top three cancers for women younger than 45 years, with the average age of death at 59 years of age. The highest burden of disease is in low-to-middle income countries (LMICs), responsible for 90% of the 311,000 cervical cancer deaths in 2018. This growing health disparity is due to the lack of quality screening and treatment programs, low human papillomavirus (HPV) vaccination rates, and high human immunodeficiency virus (HIV) co-infection rates. To address these gaps in care, we need to develop a clear understanding of the resources and capabilities of LMICs' health care facilities to provide prevention, early diagnosis through screening, and treatment for cervical cancer. Objectives This project aimed to assess baseline available cervical cancer prevention, early diagnosis, and treatment resources, at facilities designated as Health Center III or above, in Gulu, Uganda. Methods We adapted the World Health Organization's Harmonized Health Facility Assessment for our own HFA and grading scale, deploying it in October 2021 for a cross-sectional analysis of 21 health facilities in Gulu. Results Grading of Health Center IIIs (n = 16) concluded that 37% had "excellent" or "good" resources available, and 63% of facilities had "poor" or "fair" resources available. Grading of Health Center IVs and above (n = 5) concluded that 60% of facilities had "excellent" or "good" resources, and 40% had "fair" resources available. Discussion The analysis of health facilities in Gulu demonstrated subpar resources available for cervical cancer prevention, early diagnosis, and treatment. Focused efforts are needed to expand health centers' resources and capability to address rising cervical cancer rates and related health disparities in LMICs. The development process for this project's HFA can be applied to global cervical cancer programming to determine gaps in resources and indicate areas to target improved health equity.